Comparing global motor characteristics in children and adults with childhood apraxia of speech to a cerebellar stroke patient: evidence for the cerebellar hypothesis in a developmental motor speech disorder. (3rd April 2021) - Peter, Beate; Bruce, Laurel; Raaz, Caitlin; Williams, Emma; Pfeiffer, Allie; Rogalsky, Corianne
ABSTRACT: Individuals with childhood apraxia of speech (CAS) have motor deficits in systems beyond speech and also global deficits in sequential processing, consistent with cerebellar dysfunction. We investigated the cerebellar hypothesis of CAS in 18 children and adolescents with CAS, 11 typical controls, an adult with a probable CAS history, and an adult with a history of a cerebellar stroke. Compared to the controls, children and adolescents with CAS had the greatest difficulty with rapid syllable repetition when alternating between two different syllables types, less difficulty when switching among three different syllables, and no difficulty when repeating the same syllable. They also showed difficulty with alternating but not repetitive key tapping. Motor speeds during the syllable repetition and key tapping tasks where correlated, consistent with a central motor delimiter that governs both systems. Participants with CAS obtained low scores in a test of fine motor ability, where the tasks required rapid integration of complex hand movement sequences. The adult with the probable CAS history obtained motor performance scores that generally resembled those in the children and adolescents with CAS, consistent with motor deficits that persist into adulthood. The participant with the cerebellar stroke history showed deficits in tests of fine and gross motor ability as well as balance. His repetitive and alternating key tapping was slow in the ipsilateral hand relative to the stroke lesion. The shared deficits in sequential motor functions among all participants with CAS and the cerebellar stroke patient are consistent with persisting cerebellar dysfunctions in CAS.